In the digital era, architectural distortion remains a challenging radiological task. Issue 1 (January 2016) - Suleiman, W.I.; McEntee, M.F.; Lewis, S.J.; Rawashdeh, M.A.; Georgian-Smith, D.; Heard, R.; Tapia, K.; Brennan, P.C.
Abstract : Aim: To compare readers' performance in detecting architectural distortion (AD) compared with other breast cancer types using digital mammography. Materials and methods: Forty-one experienced breast screen readers (20 US and 21 Australian) were asked to read a single test set of 30 digitally acquired mammographic cases. Twenty cases had abnormal findings (10 with AD, 10 non-AD) and 10 cases were normal. Each reader was asked to locate and rate any abnormalities. Lesion and case-based performance was assessed. For each collection of readers (US; Australian; combined), jackknife free-response receiver operating characteristic (JAFROC), figure of merit (FOM), and inferred receiver operating characteristic (ROC), area under curve (Az) were calculated using JAFROC v.4.1 software. Readers' sensitivity, location sensitivity, JAFROC, FOM, ROC, Az scores were compared between cases groups using Wilcoxon's signed ranked test statistics. Results: For lesion-based analysis, significantly lower location sensitivity ( p =0.001) was shown on AD cases compared with non-AD cases for all reader collections. The case-based analysis demonstrated significantly lower ROC Az values ( p =0.02) for the first collection of readers, and lower sensitivity for the second collection of readers ( p =0.04) and all-readers collection ( p =0.008), for AD compared with non-AD cases. Conclusions: The current work demonstrates that AD remains a challenging task for readers, even in the digital era. Highlights: Architectural Distortion interpretation remains challenging for readers even with digital acquisition. Significantly lower location sensitivity and sensitivity values for the AD were shown.